Increased dosage of Ink4/Arf protects against glucose intolerance and insulin resistance associated with aging. Issue 1 (5th December 2012) - González‐Navarro, Herminia; Vinué, Ángela; Sanz, María Jesús; Delgado, Mercedes; Pozo, Miguel Angel; Serrano, Manuel; Burks, Deborah J.; Andrés, Vicente
Summary Recent genome‐wide association studies have linked type‐2 diabetes mellitus to a genomic region in chromosome 9p21 near the Ink4/Arf locus, which encodes tumor suppressors that are up‐regulated in a variety of mammalian organs during aging. However, it is unclear whether the susceptibility to type‐2 diabetes is associated with altered expression of the Ink4/Arf locus. In the present study, we investigated the role of Ink4/Arf in age‐dependent alterations of insulin and glucose homeostasis using Super‐Ink4/Arf mice which bear an extra copy of the entire Ink4/Arf locus. We find that, in contrast to age‐matched wild‐type controls, Super‐Ink4/Arf mice do not develop glucose intolerance with aging. Insulin tolerance tests demonstrated increased insulin sensitivity in Super‐Ink4/Arf compared with wild‐type mice, which was accompanied by higher activation of the insulin receptor substrate (IRS)‐PI3K‐AKT pathway in liver, skeletal muscle and heart. Glucose uptake studies in Super‐Ink4/Arf mice showed a tendency toward increased 18F‐fluorodeoxyglucose uptake in skeletal muscle compared with wild‐type mice (P = 0.079). Furthermore, a positive correlation between glucose uptake and baseline glucose levels was observed in Super‐Ink4/Arf mice (P < 0.008) but not in wild‐type mice. Our studies reveal a protective role of the Ink4/Arf locus against the development of age‐dependent insulin resistance and glucose intolerance.